2018
DOI: 10.1038/s41586-018-0374-x
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype engineering by chromosome fusion leads to reproductive isolation in yeast

Abstract: Extant species have wildly different numbers of chromosomes, even among taxa with relatively similar genome sizes (for example, insects). This is likely to reflect accidents of genome history, such as telomere-telomere fusions and genome duplication events. Humans have 23 pairs of chromosomes, whereas other apes have 24. One human chromosome is a fusion product of the ancestral state. This raises the question: how well can species tolerate a change in chromosome numbers without substantial changes to genome co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(128 citation statements)
references
References 38 publications
6
121
0
1
Order By: Relevance
“…Independent of sequence composition, we expect the upper length limit of bacterial or mammalian constructs assembled and maintained in yeast to be well over 1 Mb, as has been previously reported (5,35). Our theory is based on recent work demonstrating that yeast tolerates linear chromosomes ranging in length from 6-12 Mb (36,37), suggesting that DNA in this size range is not too long for accurate replication and segregation at cell division. Increasing the size of assemblons in yeast will require new approaches to efficiently deliver the constructs to mammalian cells, as large constructs will be subject to shear forces when manipulated in vitro.…”
Section: Discussionsupporting
confidence: 55%
“…Independent of sequence composition, we expect the upper length limit of bacterial or mammalian constructs assembled and maintained in yeast to be well over 1 Mb, as has been previously reported (5,35). Our theory is based on recent work demonstrating that yeast tolerates linear chromosomes ranging in length from 6-12 Mb (36,37), suggesting that DNA in this size range is not too long for accurate replication and segregation at cell division. Increasing the size of assemblons in yeast will require new approaches to efficiently deliver the constructs to mammalian cells, as large constructs will be subject to shear forces when manipulated in vitro.…”
Section: Discussionsupporting
confidence: 55%
“…As S. cerevisiae is tolerant to variations in the number of native chromosomes (27)(28)(29), the observed slower growth phenotype for four of the SynCh strains might be specific to the SynCh design. It has been previously shown that the size of artificial chromosomes affect their stability (30)(31)(32)(33).…”
Section: Application Of Synthetic Chromosomes As Dna Landing Padsmentioning
confidence: 98%
“…Supernumerary SynChs can be attractive landing pads to add, remove or modify functionalities. While recent chromosome engineering efforts have demonstrated that native S. cerevisiae chromosomes are extremely robust to large changes in their size and number (27,28), very little is known about S. cerevisiae's tolerance to in vivo synthetic chromosome editing (19). The 50 Kb and 100 Kb SynChs carried by strains IMF2 and IMF6 respectively, were used as landing pads for the integration of an additional 35 Kb of noncoding DNA (Fig.…”
Section: Application Of Synthetic Chromosomes As Dna Landing Padsmentioning
confidence: 99%
“…Recently, two studies described S. cerevisiae strains with a dramatically reduced number of chromosomes: from 16 to as few as 1 or 2 chromosomes [50,51]. Chromosome fusions were induced via CRISPR-Cas9-mediated deletion of telomeres and centromeres, and except for a few single-nucleotide polymorphisms and the loss of the centromeres and telomere sequences, the genomic content of the resulting isolates is similar to the wildtype strain [51]. RNA-sequencing revealed that gene expression is similar to wild-type and only 0.5% of the genes were differentially expressed, despite that HiC contact maps showed that the isolate with 1 chromosome had a completely different structural organization in the nucleus.…”
Section: Neocentromere Stains Exhibit Impaired Growth and At Elevatedmentioning
confidence: 99%
“…centromeres could be carried out, leading to a C. deuterogattii strain with only one or a few chromosomes, as was recently reported in S. cerevisiae[50,51].…”
mentioning
confidence: 95%